2018
DOI: 10.3390/nu10040437
|View full text |Cite
|
Sign up to set email alerts
|

A Specific Melon Concentrate Exhibits Photoprotective Effects from Antioxidant Activity in Healthy Adults

Abstract: Skin is the largest body organ and the first barrier to exogenous threats. This organ is constantly exposed to external factors such as ultraviolet radiation, which induces many adverse effects including sunburn, depigmentation, photo aging, photo immune suppression, and even skin cancer. Antioxidants seem to be good candidates in order to reduce ultraviolet-mediated damages and to prevent the health consequences of ultraviolet exposure. The present investigation aims to further characterize the potential skin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 45 publications
2
18
0
5
Order By: Relevance
“…Conversely, the data demonstrated that the supplementation enabled to fully normalize all four parameters. These results confirmed and extended previous reports on the beneficial effects of melon concentrate supplementation in models subjected to stressful conditions (11,17,34).…”
Section: Discussionsupporting
confidence: 92%
“…Conversely, the data demonstrated that the supplementation enabled to fully normalize all four parameters. These results confirmed and extended previous reports on the beneficial effects of melon concentrate supplementation in models subjected to stressful conditions (11,17,34).…”
Section: Discussionsupporting
confidence: 92%
“…Conversely, the data demonstrated that the supplementation enabled all four parameters to be fully normalized. These results confirmed and extended previous reports on the beneficial effects of melon concentrate supplementation in models subjected to stressful conditions, including humans with perceived stress, horses subjected to an intense physical exercise, obese hamsters or spontaneously hypertensive rats [13,15,17,19,40].…”
Section: Discussionsupporting
confidence: 90%
“…However, we can consider that these foods are not likely to be appreciated for a routine use by many consumers for reasons of caloric content, taste and, in the case of red wine, toxicity. A photoprotective activity was also found with Polypodium Leucotomos extract , green tea extract , dried melon Juice concentrate and algal extracts . However, in these cases, only the polyphenolic fraction of the extract was administered.…”
Section: Discussionmentioning
confidence: 99%